Diversity on U.S. Public and Commercial TV in Authorial and Executive-Produced Social-Issue Documentaries. Issue 3 (3rd July 2018) - Borum Chattoo, Caty; Aufderheide, Patricia; Merrill, Kenneth; Oyebolu, Modupeola
Abstract : Where are diverse makers and subjects most likely to be found in U.S. TV documentary? This study compares commercial and public TV series, and also anthology formats ("authorial" series) and executive-produced formats. A content analysis for characters and makers showed that public TV authorial series are more diverse than either commercial or other public TV series. Independent documentaries have diversity value both in commercial and public TV settings.